Acute pyelonephritis with candidemia caused by fluconazole resistant candida albicans - Periyasamy, Petrick; Shanmugam, Prapatricca; Kori, Najma; Zainulabid, Ummu Afeera (Elsevier, 2023)
An increasing number of azole-resistant Candida albicans strains have arisen due to the evolution of acquired resistance and an epidemiological shift toward less vulnerable species. Here we highlight a case of acute pyelonephritis with candidemia caused by fluconazole-resistant Candida albicans in a patient with no previous exposure to antifungals.